Możliwości edukacyjne mniejszości etnicznych w wielokulturowych Chinach. Jedność, różnorodność czy może krytyczny pluralizm? - Mańkowska, Anna (Kultura-Społeczeństwo-Edukacja, 2020)
This article explores current issues of minority education in China, especially in the context of religion and language education. In the first part of the article, the author describes (1) cultural and political framework of Chinese education in general and (2) current educational conditions, also discussing differences in educational attainment for minority groups in China. The second part of the article presents the situation of minority religions, which is not really recognised in state schooling in China. The author shows educational examples from the Tibet region and from Muslim education. The third part of the article explores another major challenge related to ethnic minority schooling, which is language diversity. In the final part of the paper, the author tries to comment on Chinese minority education dilemmas and concludes with some social recommendations.